Rancang Bangun Sterilisasi Autoclave Menggunakan Metode Dry Heat Arduino Uno Pada Alat Kedokteran Gigi (Jurnal JEETech, 2025)
Sterilization is an important process in dentistry to ensure that the instruments used are free from pathogenic microorganisms. This study aims to design and build an Autoclave sterilization system using the dry heat method based on Arduino Uno. This system is designed to provide an effective and efficient solution in the sterilization process of dental instruments. The method used in this study involves designing hardware and software integrated with Arduino Uno. The hardware consists of heating elements, temperature sensors, and control systems designed to regulate temperature accurately and consistently. Sterilization of dental instruments is very important to maintain cleanliness and prevent cross-infection. This final project is entitled "Design and Construction of Autoclave Sterilization Using the Arduino Uno-Based Dry Heat Method on Dental Instruments". The main objective of this study is to design an effective and efficient sterilization tool by utilizing the dry heat method which is safer than conventional steam-based methods. The design of this autoclave uses the Arduino Uno microcontroller as the main controller of the system, which functions to regulate the temperature and sterilization time automatically. Temperature sensors and heating elements are integrated to maintain the temperature at the optimum range (100-150°C) required in dry heat sterilization. In addition, a user-friendly interface is added to facilitate monitoring of the sterilization process. It is expected that this tool is capable  to carry out the sterilization process effectively in a shorter time, without sacrificing the quality of sterilization. This system offers more precise control and can be customized according to user needs, making it an ideal solution for dental clinics with limited budgets. Thus, this device is expected to be a useful innovation in improving hygiene standards in dental clinics, in accordance with the adage "Innovation is the key to the future" reminding us that technological advances, such as those applied in this project, can bring about major changes in the healthcare industry.